Bothriochloa jainii Deshpande et Hemadri-a New Grass from the Sahyadri Ranges, Maharashtra State - Deshpande, U. R.; Hemadri, Koppula (Indian Forester, 1971)
Bothriochloa jainii Deshpande et Hemadri, a new grass collected from different localities along the Sabyadri ranges of Western ghats is described with illustrations.